The efficacy and safety of cuttlebone for lowering serum phosphate in patients with end-stage renal disease: a meta-analysis of randomized controlled trials - Chen, Hsiao-Tien; Hung, Kuo-Chuan; Hsu, Chin-Wei; Chen, Jui-Yi; Liu, Chien-Cheng; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Pharmacology, 2023)
The efficacy of cuttlebone for treating hyperphosphatemia in patients with end-stage renal disease and its safety remained unclear.Methods: Randomized controlled trials comparing the efficacy of cuttlebone with conventional interventions were retrieved from MEDLINE, EMBASE, Cochrane Library, Airiti Library, and other major Chinese databases until February 1, 2023. The primary outcome was circulating phosphate concentration, while secondary outcomes included circulating calcium and intact parathyroid hormone (iPTH) levels, calciumphosphorus product, and treatment-related side-effects.Results: Analysis of nine studies published between 2000 and 2019 including 726 participants showed a lower circulating phosphate concentration in the cuttlebone group than in controls [mean difference (MD)=-0.23, 95% CI: -0.39 to -0.06, p=0.006, I 2 =94%, 726 patients] and a dose-dependent effect of cuttlebone against hyperphosphatemia. Therapeutic benefits were noted after both short-term (1-2 months) and long-term (3-6 months) treatments. Besides, patients receiving hemodialysis showed a better response to cuttlebone than those receiving peritoneal dialysis. There was no difference in circulating calcium level (MD=0.03, 95% CI: -0.01 to 0.07, p=0.17, I 2 =34%, 654 patients), while patients receiving cuttlebone showed lower circulating iPTH level and calcium-phosphorus product (MD=-43.63, 95% CI: -74.1 to -13.16, p=0.005, I 2 =76%, 654 patients), (MD=-0.38, 95% CI: -0.38 to -0.01, p=0.04, I 2 =83%, 520 patients). No difference in the risks of constipation, gastrointestinal discomfort, and elevated blood calcium was noted between the two groups.Compared with conventional phosphate-binding agents, cuttlebone more efficiently suppressed hyperphosphatemia with a dose-dependent effect. The limited number of included studies warrants further clinical investigations to verify our findings.